Factors affecting the development of methodological competence of students majoring in philology while teaching interpretation & translation - Т. Д. Пасічник (Іноземні мови, 2019)
The relevance of the problem of forming the methodological competence of students majoring in philology in teaching translation & interpretation has been substantiated. The factors determining the importance of scientific research into the education of interpreter and translator trainers have been defined. They include the social demand for professional translators and interpreters, the need for qualified interpreter and translator trainers, the changes in the modern education paradigm, the increasing importance of autonomous work in educational process. The literature review devoted to psychological, didactic, translational, and methodological aspects of the above mentioned problem has been conducted. The following problems are in the process of their scientific development: the structure of methodological competence of translator & interpreter trainers, the problem of trainer-led and autonomous work of students aimed at forming their methodological competence in teaching translation, the criteria for the selection of educational material, the system of exercises and tasks for forming methodological competence of students majoring in philology, the criteria for assessing the level of formation of this competence. It has been found that the most advanced requirements for the qualification level of interpreter and translator trainers are not considered in recent research studies. The expediency of the competency-based approach to the professional training of translators in accordance with the international educational standards has been proved. It has been determined that the formation of methodological competence of pre-service interpreter and translator trainers must be systematic: the objectives, principles, content, types of classroom and autonomous work on mastering methodological competence, the system of exercises and tasks must be defined. The concept for further studies on the methodological competence of students majoring in philology in teaching interpretation & translation has been substantiated.